STUDIES ON THE STORAGE OF POOLED PLATELETS IN NON DOP PVC CONTAINERS - C.S.BHASKARAN NAIR; R.VIDYA; P.M.ASHALATHA (International Journal of Pharma and Bio Sciences, 2014)
There is an increasing demand for blood bag systems for the storage of pooled platelets from at least six units of blood for the treatment of bleeding cytopenia patients. PVC plasticized with DEHP, TEHTM, DNDP, BTHC and polyolefines are being used for the storage of platelets. However PVC containers of 1.0 to 1.2 litre capacity plasticised with BTHC have been found to be the best option to meet the stringent physical and chemical characteristics needed and hence such pooling bags are marketed by all reputed blood bag manufacturers. BTHC plasticiser is expensive, has a not too pleasant smell , has high leachability into blood plasma and there are problems relating to sterilization by steam. Blood bags made with this plasticiser have been reported to cause allergic reactions. In an effort to overcome these short comings, we have developed a new type of container made using PVC of Ultra High Molecular Weight, plasticised with the non DOP, non toxic plasticiser 1,2 - Cyclohexane dicarboxylic acid, di isononyl ester [DINCH] developed by M/s BASF.Blood of the same type collected from six voluntary blood donors in SAGM TAB bags made using PVC plasticized with the new plasticizer were separated by the buffy coat method and pooled using the train system to obtain pooled platelets which were leucodepleted by filtration and collected in containers of 1200ml capacity for test A standard platelet pooling bag of 1200ml capacity was used as control. Haematological, biochemical and aggregation characteristics of the stored platelet concentrates in these bags were studied. The results indicate that 1200ml containers made using DINCH plasticized Ultra High Molecular Weight PVC were well suited for the storage of at least six units of pooled platelets for up to seven days.The results of our studies are presented in this paper.